Widyowati, Dyah PENGARUH KOMPETENSI PROFESIONAL DOSEN DAN FASILITAS PERKULIAHAN TERHADAP PRESTASI MAHASISWA POLITEKNIK NSC SURABAYA (JBT (JURNAL BISNIS dan TEKNOLOGI), 2014)
This riset analyzes the influence of professionalism of lecturers and lecture facilities on student achievement. Results found by using multiple regression analysis, showed that all the lecturers have sufficient professional competence in teaching, professional competence of faculty shortages seen in the implementation of tri dharma college in the field of research with not involve students in the study. Similarly, lectures facilities indicate that adequate facilities exist in the implementation of teaching and learning activities, only need to consider the supporting facilities of sports activities. All the results showed no influence of the professional competence of lecturers and lecture facilities on student achievement.